2014
DOI: 10.1007/978-1-4939-2080-8_1
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Basis of Total Internal Reflection Fluorescence (TIRF) Microscopy and Its Cellular Applications

Abstract: Total internal reflection fluorescence (TIRF) microscopy has gained popularity in recent years among cell biologists due to its ability to clearly visualize events that occur at the adherent plasma membrane of cells. TIRF microscopy systems are now commercially available from nearly all microscope suppliers. This review aims to give the reader an introduction to the physical basis of TIRF and considerations that need to be made when purchasing a commercial system. We explain how TIRF can be combined with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Having observed these effects exerted by SMIs on cell adhesion and based on previous knowledge that cell surface TG2 promotes integrin clustering (20), we next evaluated how targeting TG2-FN interaction impacts integrins' organization at the interface with FN. TIRF microscopy, which allows high-resolution scanning at the cell-glass substrate interface through an evanescent light wave effect (21,22) demonstrated that b1 integrins distribute evenly after OVCAR5 cells' attachment to FN-coated substrate (Fig. 4D, top; Supplementary Fig.…”
Section: Smis Prevent the Formation Of Stable Cell Contacts With The Fnmentioning
confidence: 99%
“…Having observed these effects exerted by SMIs on cell adhesion and based on previous knowledge that cell surface TG2 promotes integrin clustering (20), we next evaluated how targeting TG2-FN interaction impacts integrins' organization at the interface with FN. TIRF microscopy, which allows high-resolution scanning at the cell-glass substrate interface through an evanescent light wave effect (21,22) demonstrated that b1 integrins distribute evenly after OVCAR5 cells' attachment to FN-coated substrate (Fig. 4D, top; Supplementary Fig.…”
Section: Smis Prevent the Formation Of Stable Cell Contacts With The Fnmentioning
confidence: 99%
“…Based on the intrinsic features of evanescent illumination, the TIRF image depicts the ventral side of the plasma membrane without interference coming from intracellular fluorescence signals (Fig. S1C) (Poulter et al, 2015). The brightness of the monomeric and dimeric mEGFP tags was calibrated using two control constructs encoding glycosylphosphatidylinositol (GPI)anchored mEGFP and mEGFP-mEGFP, that served as reliable standards in previous studies on cell surface receptors (Hellriegel et al, 2011).…”
Section: Ncam and Fgf2 Induce The Formation Of Fgfr1 Complexes With Dmentioning
confidence: 99%
“…FGFR1-mEGFP population on the ventral cell membrane was imaged by TIRF microscopy, taking advantage of the short penetration of evanescent illumination (Poulter et al, 2015) HeLa cells were serum-starved overnight and imaging started immediately after adding the ligands. Cells with exceedingly high fluorescence (i.e.…”
Section: Tirf Microscopymentioning
confidence: 99%
“…Depending on refractive indices, the AOI, the wavelength and the polarization of the light source, this evanescent field reaches into the probe with a typical penetration depth of 40200 nm, and a single exponential decay. Since its introduction in fluorescence microscopy by Daniel Axelrod , TIRF microscopy has demonstrated favorable properties in numerous applications, applying living cells or reconstituted proteins (for review see Reference ). TIRF illumination through objectives with high numerical aperture, commonly referred to as objective‐type TIRF microscopy, has become a widespread standard to image signaling events during stimulation of cells with neurotransmitters, hormones, or other modulators .…”
Section: Introductionmentioning
confidence: 99%